Watt loss in three-phase transformers with circular and hexagonal forming contours of twisted spatial magnetic core rods - E.A. Avdieieva (National Technical University "Kharkiv Polytechnic Institute", 2014)
For spatial three-phase axial electromagnetic systems with circular and hexagonal cross-section configurations of twisted butt-end magnetic core rods, analytical dependences for optimal geometrical relations determination over the transformer minimum watt loss criterion are obtained, comparative analysis of the systems energy efficiency made.